Massively parallel sequencing of short tandem repeats—Population data and mixture analysis results for the PowerSeq™ system. (September 2016) - van der Gaag, Kristiaan J.; de Leeuw, Rick H.; Hoogenboom, Jerry; Patel, Jaynish; Storts, Douglas R.; Laros, Jeroen F.J.; de Knijff, Peter
Highlights: Sequencing of STRs reveals substantial variation in addition to length variation. Sequence variation of 17 STRs was assessed for three globally dispersed populations. Stutter ratios of complex STR alleles with the same length can vary substantially. Minor mixture contributions of 1% are recovered but are exceeded by stutters reads. MPS STR analysis of minor mixture contributions down to 5% is routinely feasible. Abstract: Current forensic DNA analysis predominantly involves identification of human donors by analysis of short tandem repeats (STRs) using Capillary Electrophoresis (CE). Recent developments in Massively Parallel Sequencing (MPS) technologies offer new possibilities in analysis of STRs since they might overcome some of the limitations of CE analysis. In this study 17 STRs and Amelogenin were sequenced in high coverage using a prototype version of the Promega PowerSeq™ system for 297 population samples from the Netherlands, Nepal, Bhutan and Central African Pygmies. In addition, 45 two-person mixtures with different minor contributions down to 1% were analysed to investigate the performance of this system for mixed samples. Regarding fragment length, complete concordance between the MPS and CE-based data was found, marking the reliability of MPS PowerSeq™ system. As expected, MPS presented a broader allele range and higher power of discrimination and exclusion rate. The high coverage sequencing data were used to determine stutter characteristics for all loci and stutter ratios were compared to CE data. The separation of alleles with the same length but exhibiting different stutter ratios lowers the overall variation in stutter ratio and helps in differentiation of stutters from genuine alleles in mixed samples. All alleles of the minor contributors were detected in the sequence reads even for the 1% contributions, but analysis of mixtures below 5% without prior information of the mixture ratio is complicated by PCR and sequencing artefacts.